The Role of Fintech as a Mediator in the Influence of Economic Literacy on Impulsive Buying Behavior - Muhammad Miftah Farid; Fatih Allam Misbah; Siti Mazilatus Sholikha; Deddy Setiawan; Vina Budiarti Mustika Sari; M. Riadhos Solichin; Naning Eko Noviana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the role of fintech as a mediator in the influence of economic literacy on impulsive buying behavior among consumers. Economic literacy is considered an important factor that can influence consumer purchasing behavior, especially in making wise financial decisions. However, technological advances in the financial sector, especially fintech, have also played a role in facilitating impulse buying behavior through the ease of digital transactions and quick access to financial services. This study uses a quantitative approach with a survey method involving 250 respondents. The data was analyzed using a path analysis model to evaluate the direct influence of economic literacy on impulse buying, as well as the mediation role played by fintech. The results show that economic literacy has a negative influence on impulsive buying behavior, but fintech plays a significant role as a mediator that strengthens impulse buying tendencies, even though individuals have good economic literacy. These findings have implications for the development of financial literacy policies and fintech regulations to reduce the risk of consumptive behavior in the digital era.